Technical Note: Performance of CyberKnife® tracking using low‐dose CT and kV imaging. Issue 12 (28th October 2020) - Nano, Tomi F.; Capaldi, Dante P. I.; Yeung, Timothy; Chuang, Cynthia F.; Wang, Lei; Descovich, Martina
Abstract : Purpose: To investigate the effects of CT protocol and in‐room x‐ray technique on CyberKnife ® (Accuray Inc.) tracking accuracy by evaluating end‐to‐end tests. Methods: End‐to‐end (E2E) tests were performed for the different tracking methods (6D skull, fiducial, spine, and lung) using an anthropomorphic head phantom (Accuray Inc.) and thorax phantom (CIRS Inc.). Bolus was added to the thorax phantom to simulate a large patient and to evaluate the performance of lung tracking in a more realistic condition. The phantoms were scanned with a Siemens Sensation Open 24 slice CT at low dose (120 kV, 70 mAs, 1.5 mm slice thickness) and high dose (120 kV, 700 mAs, 1.5 mm slice thickness) to generate low‐dose and high‐dose digitally reconstructed radiographs (DRRs). The difference in initial phantom alignment, Δ(Align), and in total targeting accuracy, E2E, were obtained for all tracking methods with low‐ and high‐dose DRRs. Additionally, Δ(Align) was determined for different in‐room x‐ray imaging techniques (0.5 to 50 mAs and 100 to 140 kV) using a low‐dose lung tracking plan. Results: Low‐dose CT scans produced images with high noise; however, for these phantoms the targets could be easily delineated on all scans. End‐to‐end results were less than 0.95 mm for all tracking methods and all plans. The greatest difference in initial alignment Δ(Align) and E2E results between low‐ and high‐dose CT protocols was 0.32 and 0.24 mm, respectively. Similar results were observed with a large thorax phantom. Tracking using different in‐room x‐ray imaging techniques (mAs) corresponding to low exposures (resulting in high image noise) or high exposure (resulting in image saturation) had alignment accuracy Δ(Align) greater than 1 mm. Conclusions: End‐to‐end targeting accuracy within tolerance (<0.95 mm) was obtained for all tracking methods using low‐dose CT protocols, suggesting that CT protocol should be set by target contouring needs. Additionally, high tracking accuracy was achieved for in‐room x‐ray imaging techniques that produce high‐quality images.